The Influence of Leadership and Competency Development on Employee Performance at PT Sustraco Adikreasi - Ramadhan, Muhammad Iqbal; Sriminarti, Nurul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to determine the effect of leadership and competency development on employee performance at PT. Sustraco Adikreasi. Leadership and competency development are two essential aspects of human resource management believed to contribute to optimal performance improvement. This research uses a quantitative method with an associative approach. Data were collected through questionnaires distributed to all employees, totaling 40 respondents, using a census sampling technique. The results of data analysis show that neither leadership nor competency development has a significant partial effect on employee performance. However, when tested simultaneously, both variables have a significant influence on employee performance. This indicates that leadership and competency development can contribute positively to improving performance when implemented synergistically. Therefore, the company needs to develop an integrated strategy to enhance leadership quality and the effectiveness of competency development programs to achieve sustainable employee performance improvement.